Study on the Start-up Performance of Plate Pulsating Heat Pipe with Parallel Trapezoidal Channel - Xiahou Guowei; Xie Mingfu; Kong Fangming (Zhileng xuebao, 2015)
In order to analyze the factors which affect the start-up performance of plate pulsating heat pipe, a plate pulsating heat pipe with parallel trapezoidal channel was experimentally investigated in the forced air convection cooling conditions. Results indicate that heat pipe start-up behavior at low heating power are temperature rise steadily and jump, and the jump case is divided into two categories: the temperature of evaporator and condensation rise steadily and gradually declined; while heat pipe start-up behavior at high heating power is mainly temperature jump. In addition, the full start-up temperature of heat pipe rises with the increased liquid filling ratio and inclination angle, it has nothing to do with the heating power. Specially, heating power influences the start-up speed. The higher heating power leads to the faster heat pipe start-up.